The State of Energy Research in Colombia: A View from the Research Groups - Jiménez-García, Francy Nelly; Restrepo-Franco, Alejandra María; Mulcue-Nieto, Luis Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article presents the state of research in Colombia on energy issues from the review, systematization and analysis of the results of the research groups. The information was obtained from the Scienti platform of Colciencias of a sample of research groups that claim to have lines of interest in energy. Three categories were considered for the analysis of the information: geographical location of the groups and their classification; research interests determined from the proposed lines of research; and scientific production of the groups.  It was found that 75 % of the groups are in 4 of the 32 departments of the country and 90 % belong to higher education institutions. There is diversity in terms of research interests, with four main lines of action: energy and power, energy management, hydrocarbons and renewable energies. The scientific production is centered basically in scientific articles, books and development of projects, as for patents the results are scarce. In relation to ER, the scientific production began to emerge from 1999 and has experienced a linear growth. It is possible to identify that although there is established research on energy issues from higher education institutions and some companies in the energy sector, advances related to renewable energies are still incipient; there is a road ahead which is fertilized with the new regulations that have been given in the country.